MiR-873-5p: A Potential Molecular Marker for Cancer Diagnosis and Prognosis - Zou, Yuhao; Zhong, Chenming; Hu, Zekai; Duan, Shiwei (Frontiers in Oncology, 2021)
miR-873 is a microRNA located on chromosome 9p21.1. miR-873-5p and miR-873-3p are the two main members of the miR-873 family. Most studies focus on miR-873-5p, and there are a few studies on miR-873-3p. The expression level of miR-873-5p was down-regulated in 14 cancers and up-regulated in 4 cancers. miR-873-5p has many targeted genes, which have unique molecular functions such as catalytic activity, transcription regulation, and binding. miR-873-5p affects cancer development through the PIK3/AKT/mTOR, Wnt/β-Catenin, NF-κβ, MEK/ERK signaling pathways. In addition, the target genes of miR-873-5p are closely related to the proliferation, apoptosis, migration, invasion, cell cycle, cell stemness, and glycolysis of cancer cells. The target genes of miR-873-5p are also related to the efficacy of many anti-cancer drugs. Currently, in cancer, the expression of miR-873-5p is regulated by a variety of epigenetic factors. This review summarizes the role and mechanism of miR-873-5p in human tumors shows the potential value of miR-873-5p as a molecular marker for cancer diagnosis and prognosis.